IMPROVING STUDENTS’ SPEAKING SKILL THROUGH TWO STAY TWO STRAY STRATEGY - Meida Rabia Sihite; Iskandar Zulkarnain; Atika Suri (FKIP Universitas Al Washliyah Medan, 2021)
This study is aimed at improving students’ speaking skill through Two Stay Two Stray Strategy. This study was a classroom action research. The subject of the research was the students of class X MIA-1 at SMA Teladan Sei Rampah consisting of 32 students. The research was conducted in two cycles consisting of three meetings in each. The instruments for collecting data were speaking test, observation sheet, diary notes and questionnaire. Based on the speaking test results, students’ scores kept improving in every test. On the orientation test, the mean score was 39.5. There were no students gaining score ≥ 75. In the first meeting of Cycle I, the mean score was 43. There were no students gaining score ≥ 75. In the second meeting, the mean score was 47.3. There were no students gaining score ≥ 75. In the third meeting, the mean score was 49.36. There were no students gaining score ≥ 75. In the first meeting of Cycle II, the mean score was 57.5. The number of students gaining score ≥ 75 was 5 (15.6%). In the second meeting, the mean score was 72.78. The number of students gaining score ≥ 75 was 20 (62.5%). In the third meeting, the mean score was 82.30. The number of students obtaining score ≥ 75 was 30 (93.75%). Based on the observation sheet, diary notes, and questionnaire, it was revealed the learning process ran well. The students were active and enthusiastic in learning. Thus, Two Stay Two Stray Strategy can improve students’ speaking skill